TREATING CERVICAL CANCER WITH CINNAMON BURMANNII BARK - Sezia Marina Putri (Yayasan Pendidikan Medika Indonesia, 2021)
Cervical cancer ranks fourth as the cause of death from cancer in women. Many treatments have been done to treat cancer, especially cervical cancer. Research that is still being developed is treatment derived from plants. Medicinal plants are known to contain compounds with anticancer activities such as apoptosis and inhibit the regulation of cancer cell growth. Cinnamon Burmannii or cinnamon originating from Indonesia is a woody plant that is also used as a spice. Research has shown that cinnamon bark extract has anticancer activity. To find out more about the efficacy of cinnamon bark extract as a traditional medicine, using the method, namely literature studies from both national and international journals by summarizing the topic of discussion and comparing the results presented in the article. Cinnamon bark extract contains polyphenolic antioxidants, namely flavonoids which have anticancer activity.